Estradiol regulates expression of miRNAs associated with myogenesis in rainbow trout. (5th March 2017) - Koganti, Prasanthi P.; Wang, Jian; Cleveland, Beth; Ma, Hao; Weber, Gregory M.; Yao, Jianbo
Abstract: 17β-Estradiol (E2) is a steroid hormone that negatively affects muscle growth in rainbow trout, but the mechanism associated with this response is not fully understood. To better characterize the effects of E2 on muscle, we identified differentially regulated microRNAs (miRNAs) and muscle atrophy-related transcripts in juvenile rainbow trout exposed to E2. Small RNA-Seq analysis of E2-treated vs. control muscle identified 36 differentially expressed miRNAs including those known to be involved in myogenesis, cell cycle, apoptosis, and cell death. Some important myogenic miRNAs, such as miR-133 and miR-206, are upregulated while others like miR-145 and miR-499, are downregulated. Gene Ontology analysis of the target genes regulated by the miRNAs involved in atrophy and cell cycle indicates that E2 influence leads to expansion of quiescent myogenic precursor cell population to address atrophying mature muscle in rainbow trout during sexual development. Highlights: Thirty-six miRNAs regulated by E2 are identified in rainbow trout skeletal muscle. Muscle atrophy-related genes are regulated by miRNAs under the influence of E2. E2 regulated genes control proliferation and differentiation of myogenic precursor cells.